1980
DOI: 10.1128/jb.143.3.1384-1394.1980
|View full text |Cite
|
Sign up to set email alerts
|

Reserve carbohydrate metabolism in Saccharomyces cerevisiae: responses to nutrient limitation

Abstract: The amounts of glycogen and trehalose have been measured in cells of a prototrophic diploid yeast strain subjected to a variety of nutrient limitations. Both glycogen and trehalose were accumulated in cells deprived specifically of nitrogen, sulfur, or phosphorus, suggesting that reserve carbohydrate accumulation is a general response to nutrient limitation. The patterns of accumulation and utilization of glycogen and trehalose were not identical under these conditions, suggesting that the two carbohydrates ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
367
3
8

Year Published

1982
1982
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(397 citation statements)
references
References 42 publications
19
367
3
8
Order By: Relevance
“….fla: 00 * Nitrogen and sulfur starvation. Cells were grown to early-exponential phase in MIN medium (Lillie and Pringle, 1980) containing 2% glucose at 30°C, then shifted to nitrogenor sulfur-deficient MIN medium and cultured for 1_ up to 24 h. After 2 or 6 h, the missing nutrient was added to half of the culture. Growth and terminal phenotype of the cells were assessed as described above.…”
Section: Discussionmentioning
confidence: 99%
“….fla: 00 * Nitrogen and sulfur starvation. Cells were grown to early-exponential phase in MIN medium (Lillie and Pringle, 1980) containing 2% glucose at 30°C, then shifted to nitrogenor sulfur-deficient MIN medium and cultured for 1_ up to 24 h. After 2 or 6 h, the missing nutrient was added to half of the culture. Growth and terminal phenotype of the cells were assessed as described above.…”
Section: Discussionmentioning
confidence: 99%
“…Saccharomyces cerevisiae (strain C 276 a/a, obtained from Dr J. Pringle; for trehalase metabolism, see [5]), was grown and protoplasts were prepared as in [1,6].…”
Section: Methodsmentioning
confidence: 99%
“…utilization Trehalose is a widely distributed carbohydrate in nature which is synthesized in S. cerevisiae in response to nutrient limitation and during certain environmental stress [19][20][21][22]. Ex-perimental evidence has shown that trehalose biosynthesis in yeast is catalyzed by the trehalose synthase complex [23,24], while its endogenous intracellular hydrolysis is catalyzed by the neutral trehalase but not the acid trehalase nor Ybr0106p (Nth2p) [6,10,11].…”
Section: S Cerevisiae May Have Two Pathways For Trehalosementioning
confidence: 99%